Clinical characteristics and prognosis of 16 relapsed/refractory B-cell malignancy patients with CAR T-cell-related hyperferritinaemia - Zhou, Lanlan; Yu, Nanzhou; Li, Tongjuan; Ji, Hongyan; Jiang, Lijun; Wang, Di; Xu, Bin; Zhou, Xiaoxi (Frontiers in Oncology, 2022)
With the success of chimeric antigen receptor-modified (CAR) T cell therapy for relapsed/refractory (r/r) B cell malignancies, severe or even fatal complications after CAR-T cell infusion have emerged as nonnegligible prognosis-related factors. However, the prognosis of patients with CAR-T cell-related hyperferritinaemia is unclear. We report the efficacy and safety of CAR-T cell therapy in 16 r/r B cell malignancy patients with CAR-T cell-related hyperferritinaemia. The rates of serum ferritin levels above 10,000 ng/ml during CAR-T cell therapy were 6.2% and 14.3% in B cell non-Hodgkin’s lymphoma (B-NHL) and acute B lymphocyte leukaemia (B-ALL), respectively. These patients were characterised by extremely high tumour burden and high-risk molecular abnormalities. In lymphoma and evaluable leukaemia, the complete remission (CR) rates were 37.5% (3/8) and 83.3% (5/6), respectively. The median overall survival (OS) was 3.00 months in B-ALL and not reached in B-NHL (1-year OS rate 50%). B-NHL patients with bulky disease had a significantly worse OS than others (P=0.0069). High-grade CRS (grade 3 or higher) occurred in 56.3% of the patients, and the mortality rate was 56.25%, caused by CRS, tumour progression and infection. The peak serum ferritin level in the patients who died of CRS was significantly higher than that in the others (P=0.0168). Interestingly, in our study, glucocorticoid intervention showed little impact on the expansion of CAR-T cells. Low CR rate and high mortality were observed in patients with CAR-T cell-related hyperferritinaemia.Early glucocorticoid intervention might be a worthy attempt to improve the safety of CAR-T therapy in these patients.